Contrast-Induced Acute Kidney Injury in Patients on SGLT2 Inhibitors Undergoing Percutaneous Coronary Interventions: A Propensity-Matched Analysis - Hua, Rui; Ding, Ning; Guo, Hanqing; Wu, Yue; Yuan, Zuyi; Li, Ting (Frontiers in Cardiovascular Medicine, 2022)
Objective: Contrast-induced acute kidney injury (CI-AKI) is a common complication of patients undergoing percutaneous coronary intervention (PCI). Data regarding the influence of Sodium-glucose cotransporter-2 (SGLT2) inhibitor on the CI-AKI incidence and renal outcomes of patients undergoing PCI are limited. The aim of this study was to examine the real-world risk of CI-AKI in SGLT2 inhibitor users undergoing PCI. Methods: We used longitudinal data from the medical records of First Affiliated Hospital of Xi’an Jiaotong University. We selected SGLT inhibitor users and nonusers (patients with T2D without SGLT2 inhibitor prescription) undergoing PCI. We determined CI-AKI by the ESUR (European Society of Urogenital Radiology, AKI-ESUR) and KDIGO definition (Kidney Disease: Improving Global Outcomes, AKI-KDIGO). We performed 1:1 nearest-neighbor propensity matching and calculated unadjusted odds ratios (ORs) and adjusted ORs (aORs; accounting for covariates poorly balanced) for AKI in primary and sensitivity analyses. We compared the renal function indicators in users and nonusers at 24h, 48h and 72h post-PCI. Results: We identified 242 SGLT2 inhibitor users and 242 nonusers in the cohort. The unadjusted odds ratios of CI-AKI-ESUR were 63% lower in users (OR 0.37 [95% CI 0.18–0.68]; P = 0.01), which was unchanged (aOR 0.37 [95% CI 0.19–0.67]; P <0.01) post adjustment. These estimates did not qualitatively change across several sensitivity analyses. There was no significant difference in urea nitrogen, creatinine, and eGFR values between the two groups before PCI, as well as at 24h, while the creatinine (48h and 72h post-PCI) and CyC (24h and 48h post-PCI) were significantly lower than those in the nonuser group (P<0.05). Conclusions: Our findings do not suggest an increased risk of CI-AKI associated with SGLT2 inhibitor use in CAD patients with T2D undergoing PCI.